2022
DOI: 10.1002/art.42074
|View full text |Cite
|
Sign up to set email alerts
|

Role of Lysine‐Specific Demethylase 1 in Metabolically Integrating Osteoclast Differentiation and Inflammatory Bone Resorption Through Hypoxia‐Inducible Factor 1α and E2F1

Abstract: Objective. Hypoxia occurs in tumors, infections, and sites of inflammation, such as in the affected joints of patients with rheumatoid arthritis (RA). It alleviates inflammatory responses and increases bone resorption in inflammatory arthritis by enhancing osteoclastogenesis. The mechanism by which the hypoxia response is linked to osteoclastogenesis and inflammatory bone resorption is unclear. This study was undertaken to evaluate whether the protein lysinespecific demethylase 1 (LSD1) metabolically integrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 39 publications
(62 reference statements)
3
18
0
Order By: Relevance
“…Much of our data agrees with a study determining the role of LSD1 in human osteoclasts [22]. This group showed that knockdown of LSD1 using shRNA in human osteoclasts suppresses differentiation and decreased pathological bone resorption in an arthritis mouse model [22].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Much of our data agrees with a study determining the role of LSD1 in human osteoclasts [22]. This group showed that knockdown of LSD1 using shRNA in human osteoclasts suppresses differentiation and decreased pathological bone resorption in an arthritis mouse model [22].…”
Section: Discussionsupporting
confidence: 91%
“…This group showed that knockdown of LSD1 using shRNA in human osteoclasts suppresses differentiation and decreased pathological bone resorption in an arthritis mouse model [22]. They also demonstrated that RANKL stimulation induces LSD1 expression via the mTOR pathway [22]. While these results agreed with ours, the use of shRNAs in their study may cause off target effects and further studies would need to be performed to confirm their findings.…”
Section: Discussionsupporting
confidence: 74%
“…Results of the functional analysis indicated that carbohydrate metabolism by GM was significantly decreased, and that complex carbohydrates were absorbed and converted into simple sugars, which were further fermented to produce short-chain fatty acids such as butyric acid (49). And, after further analysis of the correlation between key predicted pathways and clinical parameters, the proteasome pathway significantly reduced in the osteoporosis group was significantly positively correlated with BMD, and could degrade HIF-1 a protein which is associated with bone erosion and expressed in RANKLstimulated osteoclast precursor cells (50). Furthermore, sphingolipid metabolism by VM, which was enriched in the osteoporosis group than the control group, is known to play a key role in the regulation of inflammation signaling pathways.…”
Section: Disscussionmentioning
confidence: 98%
“…However, Hulley et al [ 25 ] believe that HIF-1α mainly acts as a regulator of osteoclast-mediated bone resorption and has almost no effect on osteoclast differentiation. In the inflammatory environment of high-energy metabolism, lysine-specific demethylase 1 (LSD1) induced by RANKL in a rapamycin-dependent manner stabilizes the expression of HIF-1α, thus promoting glycolysis and leads to pathological bone resorption [ 26 ]. Such an interaction between HIF-1α and RANKL plays a vital role in osteoclast differentiation and physiological/pathological bone resorption mediated by osteoclast.…”
Section: The Relationship Between Hif-1α and Osteoclastsmentioning
confidence: 99%